2022
DOI: 10.1111/cpr.13326
|View full text |Cite
|
Sign up to set email alerts
|

Protective roles of cytoplasmic p21Cip1/Waf1 in senolysis and ferroptosis of lung cancer cells

Abstract: Objective Therapy‐induced senescent cancer cells increase the expression of the cyclin‐dependent kinase inhibitors p16Ink4a and p21Cip1/Waf1. Given that p21 regulates not only the cell cycle but also cell death, we investigated the roles of p21 in cell death using a p16‐negative A549 human lung adenocarcinoma cell line. Methods Senescence was induced by doxorubicin (DXR) or pemetrexed (PEM). The protein expression of p21 was examined by immunoblot. Cell death, reactive oxygen species (ROS) and lipid peroxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…In the xenograft model, we used ABT‐737 rather than ABT‐263, as they have identical specificity, 27 whereas the former can be systemically administered. We previously reported that ABT‐737 exhibited antitumor effects against drug‐induced human breast and lung cancer cells both in vitro and in vivo when combined with a CDK4/6 inhibitor and pemetrexed, respectively 29,30 . In this study, combined treatment with GEM and ABT‐737 retarded the in vivo tumor growth of AsPC‐1 cells to a greater extent than either GEM or ABT‐737 monotherapy (Figure 6).…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…In the xenograft model, we used ABT‐737 rather than ABT‐263, as they have identical specificity, 27 whereas the former can be systemically administered. We previously reported that ABT‐737 exhibited antitumor effects against drug‐induced human breast and lung cancer cells both in vitro and in vivo when combined with a CDK4/6 inhibitor and pemetrexed, respectively 29,30 . In this study, combined treatment with GEM and ABT‐737 retarded the in vivo tumor growth of AsPC‐1 cells to a greater extent than either GEM or ABT‐737 monotherapy (Figure 6).…”
Section: Discussionsupporting
confidence: 54%
“…We previously reported that ABT-737 exhibited antitumor effects against drug-induced human breast and lung cancer cells both in vitro and in vivo when combined with a CDK4/6 inhibitor and pemetrexed, respectively. 29,30 In this study, combined treatment with GEM and ABT-737 retarded the in vivo tumor growth of AsPC-1 cells to a greater extent than either GEM or ABT-737 monotherapy (Figure 6). We performed in vivo experiments to test the AsPC-1 combinations because a prior study reported combined effects of GEM and ABT-263 against PANC-1 cells.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations